Novel splicing mutation in the ASXL3 gene causing Bainbridge–Ropers syndrome. Issue 7 (13th April 2016) - Hori, Ikumi; Miya, Fuyuki; Ohashi, Kei; Negishi, Yutaka; Hattori, Ayako; Ando, Naoki; Okamoto, Nobuhiko; Kato, Mitsuhiro; Tsunoda, Tatsuhiko; Yamasaki, Mami; Kanemura, Yonehiro; Kosaki, Kenjiro; et al.
Abstract : Bainbridge–Ropers syndrome (BRPS) is characterized by severe developmental delay, feeding problems, short stature, characteristic facal appearance including arched eyebrows and anteverted nares, and ulnar deviation of the hands. BRPS is caused by a heterozygous mutation in the additional sex combs‐like 3 ( ASXL3 ) gene. We describe a patient with severe developmental delay, feeding problems, short stature, autism, and sleep disturbance with a heterozygous de novo splicing mutation in the ASXL3 gene. Reported disease‐causing mutations in ASXL3 are located mostly in the first half of exon 11, analogous to ASXL1 mutations of which result in Bohring–Opitz syndrome (BOS). Our findings suggest that the expression of the truncated ASXL3 protein, including ASXN and ASXH domains, give rise to BRPS, which is distinct from but overlaps with BOS. © 2016 Wiley Periodicals, Inc.